Le débat sur le statut politique des israélites en Algérie et ses acteurs (1870-1943) - Renucci, Florence (Contributions du séminaire sur les administrations coloniales (2009-2010), 2010)
Cette contribution a pour objectif de comprendre quels ont été les débats qui ont porté sur le décret Crémieux entre 1870 et 1943. Ce texte qui imposait la citoyenneté française aux israélites "indigènes" d'Algérie a dans un premier temps été controversé (1870-1939), puis, dans un second temps, abrogé avec le régime de Vichy. L'idée est de comprendre les mécanismes juridico-intellectuels qui sont mis en avant dans ces débats et leur application concrète. Cet article met en évidence la complexité des positionnements des différents acteurs (en particulier du droit) et la difficulté à les classifier.
Keywords: Judaïsme -- Mzab

Les juifs d’Algérie et la citoyenneté (1870-1902). Les enjeux d’un statut contesté - Renucci, Florence (Droit et Justice en Afrique coloniale : Traditions, productions et réformes, 2014)
Keywords: Judaïsme -- Mzab

Le passé juif de l’Algérie et l’enjeu des archives - Stein, Sarah Abrevaya (Archives Juives, 2016)
In the climax of the Algerian war of independence (1954-1962) a variety of international parties, including officials in France, Algeria, and Israel, fought to gain control over documentation of and about a small Jewish community in the Algerian Sahara. This essay considers why decolonization radically changed the fate of the papers of a community long fetishized as marginal by social scientists, policy makers, and the demographic bulk of North African Jewry. To do so, it looks back to a history of colonial law that segmented southern Algerian Jewry off from Jews of the north and explores the fierce archival battle, a component of the Algerian war of independence, over who would control the documents of Algeria’s past. Finally, this article reaches into the present day, probing how documents of the North African and Middle Eastern past continue to be used to serve various, conflicting nationalist agendas. All told, this research teaches that when it comes to studying Algerian Jewish history, the historian inevitably bumps up against an active and highly politicized, multi-party contest over the sources of the Jewish past — one laced through with the complex history of Jews’ relationship to the colonial and postcolonial order, and, indeed, power itself.
Keywords: Judaïsme -- Mzab

Black Holes, Dark Matter, and Buried Troves: Decolonization and the Multi-Sited Archives of Algerian Jewish History - Stein, Sarah Abrevaya (The American Historical Review, 2015)
Keywords: Judaïsme -- Mzab

Sur les traces des Juifs sahariens - Warscheid, Ismail (La Vie des idées, 2015)
À propos de : Sarah A. Stein, Saharan Jews and the Fate of French Algeria, Chicago
Keywords: Judaïsme -- Mzab; Recension

Juifs du Mzab (Patawet, 2010)
Juifs du Mzab Mariage Juif Les Juifs du Mzab sont une petite communauté juive d'Algérie originaire du Mzab, une région isolée située dans le Sahara...
Keywords: Judaïsme -- Mzab

The Jews of the Desert: Colonialism, Zionism, and the Jews of the Algerian M’zab, 1882-1962 - Wall, Rebecca A. (University of Michigan, 2014)
Keywords: Judaïsme -- Mzab

Mzab - Guerin, Adam (Encyclopedia of Jews in the Islamic World, 2010)
Keywords: Judaïsme -- Mzab

A desert named peace: the violence of France's empire in the Algerian Sahara, 1844-1902 - Brower, Benjamin Claude (History and society of the modern Middle East, 2011)
Keywords: Judaïsme -- Mzab

The Field of In Between - Stein, Sarah Abrevaya (International Journal of Middle East Studies, 2014)
In the spring of 1902, Miryam bint Lalu Partush appealed to military representatives in Ghardaïa, in the Mzab Valley (a valley of five fortified oasis cities in the northern Algerian Sahara, six hundred kilometers south of Algiers), for the paperwork that would allow her to undertake a six-month pilgrimage to Jerusalem with her husband, the wealthy merchant Musa (Moshe) bin Ibrahim Partush. Miryam Partush was unusual in possessing the means for such a rare, costly voyage; but notwithstanding her class, Partush's legal status was typical of most Muslims and southern Algerian Jews in Algeria. She was not a citizen, nor did she hold official papers of any kind. When Miryam Partush appealed to the military authorities in Ghardaïa, then, she was appealing for many things: for the right to leave her native valley and travel to the port of Algiers; for the papers that would allow her to cross colonial boundaries; and for the documentation that would register her liminal legal identity. Authorizing her travel, Algeria's governor-general named Partush a “non-naturalized Jew from the Mzab.” Thus did Partush embark on her six-month journey with a negative legal identity: this Jewish woman was definable, in the eyes of the law, only by what she did not possess.
Keywords: Judaïsme -- Mzab

Saharan Jews and the fate of French Algeria - Stein, Sarah Abrevaya (The University of Chicago Press, 2014)
Keywords: Judaïsme -- Mzab